O impacto da hierarquia de memória sobre a arquitetura IPNoSys - Damasceno, Alexandro Lima (Universidade Federal Rural do Semi-Árido, 2016)
Over the years, with the as technology advances, the search for improvements in the performance of computer systems is notable. The computer systems have evolved in both processing capacity and complexity of the implemented architectures. In such systems it is crucial to use memories since they are responsible for storing data to be processed. Considering an ideal environment, the memories should have a unlimited storage capacity, instant data access and the extremely low cost per bit. But in real systems the memories do not exhibit these characteristics. Storage capacity, speed and cost per bit are factors that increase in proportion to each other. One technique that is used to balance these factors and improve the performance of computer systems is the memory hierarchy. In the scenario of new technologies and proposals for new organizations of processors, a model that has been adopted by designers of computer systems is the use of MPSoCs (multiprocessor systems on chip), which has a higher energy and computational e ciency. In this scenario with many processing elements, networks using on-chip (NoC - networks-on-chip) is more e cient use of the buses. An NoC consists of a set of routers and interconnected channels forming a switched network. The cores are connected to network terminals and communication occurs through the exchange of packets. These NoCs have traditionally been exclusively designed for communication SoCs. However, a project of an unconventional architecture decided to integrate processing and communication in an NoC. This architecture is known for IPNoSys. The IPNoSys (Integrated Processing NoC System) architecture is an unconventional processor that uses networks on chip and implements processing units and routing to handle and process instructions. It takes advantage of the characteristics of NoC, such as scalability and parallel communication, for implement e ectively runs programs that exploit parallelism-level threads. Currently, IPNoSys architecture has four memory physically distributed at the corners of the network, but represent a unified addressing. Each memory module is associated with an access unit in charge of managing it. Given the current organization of IPNoSys memories, this work proposes to develop a new memory hierarchy system for IPNoSys and investigate the possible impact on performance and the programming model
Keywords: Hierarquia de memória; Arquitetura IPNoSys; Redes em chip; Memory hierarchy; IPNoSys architecture; Networks on chip; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO